Diabetes & C-Peptide Scientific and Clinical Aspects - Sima, Anders A.F (Contemporary Diabetes,, 2012)
In Diabetes & C-Peptide: Scientific and Clinical Aspects, a renowned group of leading researchers and physicians offers a comprehensive overview of the role of C-Peptide in type 1 diabetes. The book is organized in five sections. An Introductory section provides the background and key features of C-peptide's physiological function and how its deficiency contributes to complications. The second section describes up-to-date information on the biochemical and molecular actions of C-peptide, including membrane binding, interactions with insulin as well as the interaction between C-peptide and zinc and effects on microvascular vasoreactivity. The third section summarizes in vivo animal studies of the type 1 diabetic complications. The fourth section reviews the clinical efforts of C-peptide on inflammation, cardiovascular complication, neuropathy and nephropathy. Finally, in the Conclusions section, a summary of the present state of C-peptide, outstanding questions, and the likely direction of the field are offered. Developed by the foremost investigators in the rapidly moving field of C-peptide research, Diabetes & C-Peptide: Scientific and Clinical Aspects is an important contribution to the literature for all researchers and physicians concerned about type 1 diabetes.